2022
DOI: 10.1016/j.jaim.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Combating the psychological impact of COVID-19 pandemic through yoga: Recommendation from an overview

Abstract: Globally, the psychological health of the people is being affected due to the COVID-19 pandemic. Given the fact that numerous systematic reviews already exist on yoga and mental health, it becomes vital to undertake an overview on the same. The objective of the overview was to summarise the evidence from different systematic reviews of distinct yoga interventions used to improve mental health and recommend yoga practices for the same. The protocol was registered on PROSPERO (CRD42020185221). MEDLINE via Pubmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Likewise, regarding the use of self-help practices, although decreased, almost a quarter of Norwegian citizens continued to use these techniques during the lockdown. Previous research has shown that practicing yoga may lower depression, anxiety, and stress, and increase general wellbeing and peace of mind during the COVID-19 lockdown [27,28]. Furthermore, it has been reported that mindfulness may increase well-being and provide a tool for people to deal with stressful situations such as the COVID-19 pandemic [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, regarding the use of self-help practices, although decreased, almost a quarter of Norwegian citizens continued to use these techniques during the lockdown. Previous research has shown that practicing yoga may lower depression, anxiety, and stress, and increase general wellbeing and peace of mind during the COVID-19 lockdown [27,28]. Furthermore, it has been reported that mindfulness may increase well-being and provide a tool for people to deal with stressful situations such as the COVID-19 pandemic [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that practicing yoga may lower depression, anxiety, and stress, and increase general wellbeing and peace of mind during the COVID-19 lockdown [27,28]. Furthermore, it has been reported that mindfulness may increase well-being and provide a tool for people to deal with stressful situations such as the COVID-19 pandemic [28,29]. A systematic review has in addition revealed that acupuncture, traditional Chinese medicine (TCM), relaxation, and qigong were found to improved psychological symptoms like depression, anxiety, stress, sleep quality, negative emotions, and quality of life in patients already infected with COVID-19, and further improved physical symptoms like inflammation, chest pain, and respiratory function [30].…”
Section: Discussionmentioning
confidence: 99%
“…Wright K et al [37] Many studies were done to improve the mental and physical health of people during COVID-19. Kulkarni MS et al [39] concluded that yoga has beneficial effects on mental health. Yoga is an intervention in young and adult people for the treatment of both acute and chronic health problems, and also yoga is most effective in reducing symptoms of depression, anxiety, and pain, according to McCall MC et al [40].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, ref. [50] suggested the practice of yoga as a moderating factor. Several papers have investigated the role of mindfulness in the COVID-19 crisis more closely.…”
Section: Previous Evidence Collected During the Covid-19 Crisismentioning
confidence: 99%